Orality and the Archive: Teaching the Partition of India through Oral Histories - Jayagopalan, Gaana (Radical Teacher, 2016)
This article is a reflection on how select oral histories and witness accounts about the partition of India and Pakistan, especially those by Urvashi Butalia and Veena Das were used in a graduate seminar in Bengaluru. The article explores the strength of oral archives as repositories of radical enquiry that may be used in classrooms to understand the complex nature of history, historiography, and interrogate the State’s archival processes. The article explores how students began to see the potency in oral archives as a space that embodies the victimhood of partition victims as opposed to an effacement of the sufferers in most state archives of the event. It observes how the memorialisation of Partition is different in the State’s construction of partition: to the victims who recount their stories, it is the ‘everyday’ that becomes predominant as opposed to State archives that seek to represent the differences between the two nations as paramount in its processes of memorialisation. The note concludes by emphasising the need to put such oral histories to use in classroom, especially to understand the nature of suffering. Through a reading of such stories, it is proposed, an affective literacy is enabled in students’ modes of enquiry about trauma, memory and suffering. Keywords: Partition of India, affective literacy, archives, oral histories, witness narratives.